2014
DOI: 10.3389/fphys.2014.00120
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pressure and cerebral blood flow variability: friend or foe? A review

Abstract: Variability in arterial pressure and cerebral blood flow has traditionally been interpreted as a marker of cardiovascular decompensation, and has been associated with negative clinical outcomes across varying time scales, from impending orthostatic syncope to an increased risk of stroke. Emerging evidence, however, suggests that increased hemodynamic variability may, in fact, be protective in the face of acute challenges to perfusion, including significant central hypovolemia and hypotension (including hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 116 publications
(164 reference statements)
2
59
0
3
Order By: Relevance
“…). In response to dynamic changes in BP, cerebrovascular bed behaves as a ‘high‐pass filter’ system, which buffers the effects of BP fluctuations on CBF via cerebral autoregulation (CA) (Lassen ; Rickards and Tzeng ). The CA is more or less a frequency dependent phenomenon that operates more efficiently at very low frequency (< 0.05 Hz) (Aaslid et al .…”
Section: Main Determinants Of Cbfmentioning
confidence: 99%
“…). In response to dynamic changes in BP, cerebrovascular bed behaves as a ‘high‐pass filter’ system, which buffers the effects of BP fluctuations on CBF via cerebral autoregulation (CA) (Lassen ; Rickards and Tzeng ). The CA is more or less a frequency dependent phenomenon that operates more efficiently at very low frequency (< 0.05 Hz) (Aaslid et al .…”
Section: Main Determinants Of Cbfmentioning
confidence: 99%
“…Interest in biological variability has exploded over the past decade, with significant literature now focusing on neural (Wang, 2010) and cardiovascular (Lehrer and Eddie, 2013; Rickards and Tzeng, 2014) oscillations. Greater variability in biological functions is generally thought to demonstrate more intact regulatory systems that are appropriately detecting and dynamically responding to perturbation (Kitano, 2004; Lehrer and Eddie, 2013; Thayer and Lane, 2000).…”
mentioning
confidence: 99%
“…Rather, it can flexibly respond to challenge by changing stroke volume, vascular tone, and blood pressure (BP) variability in addition to or in lieu of changing HRV (Liu et al, 2004; Ma and Zhang, 2006; Rickards and Tzeng, 2014; Vaschillo et al, 2012). System redundancy ensures that the cardiovascular system can buffer itself against internal (e.g., cognitive emotional) and external (e.g., pharmacological) challenges, and thus protect the brain from stroke and the heart from myocardial infarction.…”
mentioning
confidence: 99%
“…). However, more recently Rickards and Tzeng () reviewed the role of oscillations in MAP and MCAv during hemorrhage and concluded that increased variability may protect cerebral blood flow during hypovolemia. The underlying mechanism may be that less energy is required to maintain forward flow if the flow is pulsatile versus continuous.…”
Section: Discussionmentioning
confidence: 99%